Proximal repetition in the linguistic landscape - Peckson, Philip (Philippine Journal of Linguistics, 2014)
Many walls or gates along Metro Manila’s streets have signs asking drivers not to block driveways or pedestrians not to loiter. What is interesting is that these signs are often repetitious and are spaced very close to each other. This phenomena, what I call proximal repetition, differs from standard repetition: the regular and rational spacing of signs installed by corporations or local governments. In this paper, I examine instances of proximal repetition in Metro Manila and Coron, Palawan through an analytical framework informed by politeness theory, particularly studies on nagging, and Tim Ingold’s writing on practical culture. I conclude that those who use proximal repetition in sign placement have, like naggers, status but weak power. Lastly, I provide arguments for the inclusion of proximal repetition and its counterpart, standard repetition, as salient features of the linguistic landscape, mainly because they allow the field to consider not just sociolinguistic phenomena but spatial practice as well. ​